A THE ROLE OF STUDENTS IN SUPPORTING INDONESIA BECOME QUALIFIED ECONOMIC ACTORS IN THE DIGITAL ERA - Yenni Sofiana Tambunan; Nelly Azwarni Sinaga; Sinta Veronika Hutabarat (Jurnal Ekonomi, 2022)
The potential of the e-commerce industry in Indonesia cannot be underestimated. From Ernst & Young's analysis data, it can be seen that the growth in sales value of online businesses in Indonesia increases by 40 percent every year. There are around 93.4 million internet users and 71 million smartphone device users in Indonesia (https://Kominfo.go.id). As the highest point, students must have critical thinking and be sensitive to what problems are being faced and are happening in society, then express their opinions and participate or be directly involved in solving these problems. The presence of new technology in the future will also have many impacts on the people's economy, there will be many new job vacancies, but there will also be many workers who will lose their jobs because they are no longer related or competent in the future technological era, and some fields of work will be taken over by robots.